PENGARUH ARUS KAS OPERASI, UKURAN PERUSAHAAN, DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA - , (Politeknik Sawunggalih Aji, 2023)
Earnings persistence is one component of earnings quality. This study discusses the factors affecting earnings persistence in mining sector companies listed on the IDX, with independent variables namely operating cash flow, company size, and debt levels. The purpose of this study is to test, calculate, and describe the effect of operating cash flow, company size, and debt levels on earnings persistence. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. The sampling technique used purposive sampling and obtained 14 companies with 42 research samples. The data source was obtained from the annual financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The data analysis method uses multiple linear regression analysis with SPSS 21 Software application. Based on the test results of multiple linear regression analysis, individually (partial) states that operating cash flow has a negative and not significant effect on earnings persistence, firm size has a positive and significant effect on earnings persistence, and the level of debt has a positive and significant effect on earnings persistence. While jointly (simultaneously) operating cash flow, company size, and debt levels have a positive and significant effect on earnings persistence. Based on the results of the study, then to assess the performance of the company in addition to using profits, investors and other parties can use the size of the company and the level of debt that shows the company's performance. Keywords: Operating Cash Flow, Company Size, Debt Level, Profit Persistenc